Kekerabatan Genetik Caplak Rhiphicephalus (Boophilus) microplus Asal IndonesiaBerdasarkan Sekuen Internal Transcribed Spacer-2 (GENETIC RELATIONSHIP INDONESIAN RHIPHICEPHALUS (BOOPHILUS) MICROPLUS TICK BASED ON INTERNAL TRANSCRIBED SPACER-2 SEQUENSE ) - Sahara, Ana; Prastowo, Joko; Widayanti, Rini; ., Kurniasih; Nurcahyo, Wisnu (Jurnal Veteriner; Vol 16 No 3 (2015), 2015)
Rhiphicephalus (Boophilus) microplus is important obligatory blood feeding ectoparasites transmittingmany different viral, bacterial and protozoan and plays a role as a vector of Babesia sp., The leria sp. andAnaplasma sp. in cattle. The accuracy in identifying and distinguishing interspecies and intraspeciesdiversity among parasites is needed to understand the epidemiology, biology and capacity as a vector.Variations in the DNA base sequence of the internal transcribed spacer region2 (ITS 2) has been used asa molecular marker for identification in an effort to determine phylogenetic relationships. The aim of thisstudy was to determine the ITS 2 gene nucleotide sequence of R. microplus, which was expected to beuseful for accurate identification the parasite diversity and phylogenetic relationship among many differentspecies. DNA amplification was conducted using BOO2 forward dan BOO2 reverse primers. The DNAsamples containing ITS2 region fragment of 1099 nt were derived from the nucleotide sequence multiplealignments of R.microplus and other ticks genes obtained from Gene bank using Clustal W software, andthen analyzed using the MEGA program version 6. Genetic distances based on nucleotide sequence weredetermined with Kimura 2-parameter method producing the smallest genetic distance of 0 % and 1.2 %.Construction of phylogenetic trees using the Neighbor joining method showed that ticks from variousregions in Indonesia was species complex which have a closer with R.microplus isolates from India, Laos,South Africa, China and Australia R.australis origin.
Keywords: Tick, Ectoparasite, Rhiphicephalus (Boophilus) microplus